A versatile structural analysis method for analog, digital and mixed-signal circuits - Eick, M.; Graeb, H. (2012 International Conference on Synthesis, Modeling, Analysis and Simulation Methods and Applications to Circuit Design (SMACD), 2012)
Analog as well as mixed-signal circuits are subject to many design constraints, e.g., matching constraints. We present a new approach for structural analysis that can handle analog, digital and mixed-signal circuits. It consists of a building block recognition, graph-based analyses and logic function extraction. Experimental results are provided for several digital cell libraries and a mixed-signal circuit. They show that more than 95% of the digital standard cells and a current-mode DAC are handled correctly.